Cost of cardiac stereotactic body radioablation therapy versus catheter ablation for treatment of ventricular tachycardia. Issue 9 (9th June 2022) - Wei, Chen; Boeck, Michelle; Qian, Pierre C.; Vivenzio, Todd; Elizee, Zoe; Bredfeldt, Jeremy S.; Kaplan, Robert S.; Tedrow, Usha; Mak, Raymond; Zei, Paul C.
Abstract: Aims: To compare the cost of cardiac stereotactic body radioablation therapy (SBRT) versus catheter ablation for treating ventricular tachycardia (VT). Background: Cardiac SBRT is a novel way of treating refractory VT that may be less costly than catheter ablation, owing to its noninvasive, outpatient nature. However, the true costs of either procedure are not well described, which could help inform a more appropriate reimbursement for cardiac SBRT than simply cross‐indexing existing procedural rates. Methods: Process maps were derived for the full patient care cycle of both procedures using time‐driven activity‐based costing. Step‐by‐step timestamps were collected prospectively from a 10‐patient SBRT cohort and retrospectively from a 59‐patient catheter ablation cohort. Individual costs were estimated by multiplying timestamps with capacity cost rates (CCRs) for personnel, space, equipment, consumable, and indirect resources. These were summed into total cost, which for cardiac SBRT was compared with current catheter ablation and single‐fraction lung SBRT reimbursements, both potential reference rates for cardiac SBRT. Results: The direct and total procedural costs of cardiac SBRT (7549 and 10, 621) were 49% and 54% less than those of VT ablation (14, 707 and 23, 225). These costs were significantly different from current reimbursement for catheter ablation (22, 692) and lung SBRT (6329). After including hospitalization expenses (≥15, 000), VT ablation costs at least 27, 604 more to furnish than cardiac SBRT. Conclusions: Time‐driven activity‐based costing (TDABC) can be a helpful tool for assessing healthcare costs, including novel treatment approaches. In addition to its clinical benefits, cardiac SBRT may provide significant cost reduction opportunities for treatment of VT.